The Tommy Koh reader : favourite essays and lectures - Koh, Tommy T. B. 1937- (World Scientific, 2013)
"Professor Tommy Koh is Singapore's Ambassador-at-Large at the Ministry of Foreign Affairs, Rector of Tembusu College, Special Adviser of the Institute of Policy Studies, and Chairman of the Centre for International Law, National University of Singapore. In his distinguished career, Prof Koh has served as Singapore's Permanent Representative to the United Nations, as Ambassador to the United States of America, as President of the Third UN Conference on the Law of the Sea and Chairman of the Preparatory Committee and the Main Committee of the UN Conference on Environment and Development. He was the UN Secretary-General's Special Envoy to Russia, Estonia, Latvia, and Lithuania. He chaired two dispute panels for the WTO. He was also Singapore's Chief Negotiator for the US-Singapore Free Trade Agreement. He was also the chairman of the group which drafted the Asean Charter. He chairs three committees for the National University of Singapore relating to law, Asia research and environmental management. An active patron of the arts, Prof Koh has served as Chairman of the National Heritage Board, National Arts Council and many other cultural groups. In recognition of his meritorious public service and achievements, he was conferred many honours, both locally and internationally. He has been named as Champion of the Earth in 2006 by the UN Environment Programme (UNEP). Prof Koh has been selected to receive Harvard's 2014 Great Negotiator Award sponsored by the Program on Negotiation based at Harvard Law School (an interuniversity consortium of Harvard, MIT, and Tufts) as well as Harvard's Program on the Future of Diplomacy. This collection of Prof Koh's favourite essays and lectures gives the reader an insight into his illustrious academic and diplomatic career. The volume also includes his articles on diplomacy and international law, art, culture, heritage, nature and environmental issues."--Publisher.